Evaluation of the infectivity of three porcine reproductive and respiratory syndrome virus (PRRSV) variants - Claudio Marcello Melini; Mariana Kikuti; Montserrat Torremorell; Kimberly VanderWaal; Stephanie Rossow; Jerry Torrison; Cesar A. Corzo (Veterinary Research)
Abstract Porcine reproductive and respiratory syndrome virus (PRRSV) continues to burden the US swine industry significantly. In some instances, the virus evaded biosecurity measures, remaining viable in sufficient concentrations to cause an outbreak. Little is known about differences in infectivity among viral variants. In this study, we compared the infectivity of three PRRSV variants by estimating the median infectious dose (ID50) and minimum infectious dose (MID), while also characterizing nasal and rectal shedding patterns and histologic lesions. Groups of six individually housed pigs were intranasally inoculated with 2 mL of five different concentrations (100 to 104 TCID50/mL) of inoculum per variant. Blood, rectal, and nasal swabs were collected at different time points up to 28 days post-inoculation (dpi) and tested via RT-PCR. Two animals per group were euthanized on 11 dpi and tissue samples were assessed by histopathology. The estimated ID50 based on serum RT-PCR positive pigs at 4 dpi was 102.6 TCID50/mL (95% CI 102.0, 103.2) for the L9A variant, 102.3 TCID50/mL (95% CI 101.6, 103.0) for the L1A variant, and 101.3 TCID50/mL (95% CI 100.4, 102.2) for variant L1C.5. No apparent differences were observed in shedding patterns among tested groups. However, the amount of lesions caused by variant L1C.5 was more extensive compared to those infected with the other two variants. Based on our findings, the L1C.5. variant required fewer infectious units to infect half of the inoculated pigs and resulted in more microscopic lesions confirming that PRRSV variants exhibit different levels of infectivity, virulence, and pathogenicity.